Analisis Perbandingan Penggunaan Pengkodean Low-Code dan Konvensional Pada Pengembangan Sistem Informasi Kepegawaian: Studi Kasus : PT ABC - Stieven Limanjaya; Muhammad Rachmadi (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
The creation of a web-based application management system is essential to assist organisations in maintaining their operational efficiency in the rapidly growing digital era. The purpose of this research is to apply the waterfall development method approach to the development of a web-based application management system. We compared the time efficiency and features of a low-code platform such as OutSystems and traditional coding using native PHP. By streamlining procedures for recruitment, leave, warning or dismissal data, and human resource management, the system can improve overall operational effectiveness and efficiency. This research can provide in-depth information on the efficiency of development time and overall features. Our contribution is to clarify the performance comparison in the context of application management system development between low-code platforms and traditional development approaches.